2017
DOI: 10.29313/ethos.v5i2.2334
|View full text |Cite
|
Sign up to set email alerts
|

Pemberdayaan Potensi Masyarakat Desa Cimungkal Kecamatan Wado Melalui Wirausaha Sereh Wangi

Abstract: Abstract. The main problem in the society which become the service activities partner is the not used the potential and local resources in terms of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Generally, several studies reported that lemongrass could be planted on laboratory scale, and infertile mineral soils in monoculture system (Rosman, 2012;Anwar et al, 2017;Sulaswatty et al, 2019), but has never been planted on postmining areas in Agroforestry system. The study investigated and compared the growth of lemongrass varieties planted on post-coal mining revegetation land in agroforestry and monoculture system.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, several studies reported that lemongrass could be planted on laboratory scale, and infertile mineral soils in monoculture system (Rosman, 2012;Anwar et al, 2017;Sulaswatty et al, 2019), but has never been planted on postmining areas in Agroforestry system. The study investigated and compared the growth of lemongrass varieties planted on post-coal mining revegetation land in agroforestry and monoculture system.…”
Section: Introductionmentioning
confidence: 99%
“…Diagram alir penelitian adalah sebagai berikut : Proses terjadinya kondensasi merupakan pemampatan atau pendinginan yang apabila dapat tercapai tekanan maksimum dan suhu dibawah kritis. [8] Proses terjadinya kondensasi apabila uap didinginkan menjadi cairan, akan tetapi dapat juga apabila sebuah uap dikompresi (yaitu tekanan ditingkatkan) menjadi cairan, atau mengalami suatu kombinasi dari pendinginan kompresi. Kondensasi atau pengembunan adalah perubahan wujud benda ke wujud yang lebih padat, seperti gas menjadi cairan.…”
Section: Metodologi Penelitianunclassified
“…Sereh wangi di manca Negara dikenal dengan citronella grass. Di Indonesia tanaman sereh wangi memiliki nama daerah yang berbeda-beda, disebut sereh di daerah Jawa, Madura, Sunda dan Gayo, disebut sarai di daerah Minang, disebut sorai di daerah Lampung, disebut see di daerah Bali, disebut patahampori di daerah Bima, disebut kedoung witu di daerah Sumba, disebut tenian nalai di Pulau Leti dan disebut nou sina di pulau Roti [1].…”
Section: Pendahuluanunclassified